Características fisicoquímicas y acción reductora sobre el ion férrico del zumo del fruto maduro de Physalis peruviana L. “aguaymanto”. - Vásquez Reyes, Gianinna del Pilar (2018)
The purpose of this research work is to determine the physicochemical characteristics of the juice of the mature fruit of Physalis peruviana L. "aguaymanto" and the reducing action on the ferric ion. The fruit of Physalis peruviana L. was collected in the province of Cajabamba, the juice was obtained with a liquefier extractor. Analyzes of the organoleptic characteristics, density, pH, refractive index, acid number, total soluble solids and solubility in ethanol were carried out. Also, the reducing action on the ferric ion was determined by the modified method of Oyaizu M., using as a standard the gallic acid and preparing working samples of the juice at concentrations of 200, 400, 600, 800 and 1000 mg/mL; 1 mL of the working sample was measured by mixing with 5 mL of phosphate buffer, at pH 6,6 and with 5 mL potassium ferricyanide [K3Fe (CN) 6] at 1% and after an incubation period of 20 minutes at a T ° 50 ° C, 5 mL of 10% trichloroacetic acid was added and centrifuged at 4000 rpm for 15 minutes, 5 mL of the supernatant of the solution was mixed with 5 mL of distilled water and 1 mL of ferric chloride at 1 %. The absorbance was measured at 700 nm. From the analysis of the results of the physicochemical characteristics, the ripe fruit juice of Physalis peruviana L. has a suigeneris odor, orange yellow color, bittersweet taste and viscous texture, total soluble solids 15,2%, pH 4,53%, relative density 1,0339%, acidity index 1,86%, solubility in ethanol / water is 50% v/v, refractive index is 1,353. The juice of the ripe fruit of Physalis peruviana L. "aguaymanto" has a reducing action on the ferric ion, and this varies directly with the concentration